Empowerment jako nowoczesna forma zarządzania zasobami ludzkimi w filozofii TQM - Leszczyńska, Magdalena (Empowerment as a Modern Way of Human Resources Management in the Philosophy Concept of TQM, 2008)
A form of human resources management (empowerment) must be used and results from internal needs (effective employees motivation) and external (market and clients activeness). Realization of empowerment in the TQM concept needs to create for all employees such conditions of work which increase their independence and responsibility for performers' obligations. Empowerment is a change of employees' consciousness, which influences not only their personal career development but also improvement of their work in an organization. A full sense of value, satisfaction of work and development of competition influence good relations with the clients and high quality of products. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 31, s. 69-78